PAIN PARAMETERS RELATED TO BOTH PHYSICAL ACTIVITY INTERRUPTION AND CONTINUITY IN WOMEN (Fiep Bulletin - online, 2011)
This study aimed to assess pain incidence in active elderly people, relating such occurrence to vacation time or term breaks in the extension projects carried out by institutions and community welfare programs. The study group consisted of 16 women out of the 50 participants in the "Ativa Idade" extension program, average age 64 ± 9 (DP=8,66). The pain parameters were assessed through an individual questionnaire, applied at the beginning of the program. The pain was located predominantly on the knee joint (24,39%), followed by the cervical region of the spine (17,07%), and the lumbar region of the spine (14,63%). This research found a higher number of pain occurrences, both as to incidence and prevalence, in the group that had a three-month recess than in the group that had a one-month recess only. Also, the disappearance of pain was greater in the latter. It has been found that physical inactivity, even over a short period of time, may jeopardize the quality of life of mature adults and regularly active elderly people.
Keywords: aging; inactivity; pain